Jharkhand’s mineral wealth :A catalyst for vikshit Bharat (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Jharkhand, known as the "Land of Forests," is a state rich in mineral resources that have long served as a catalyst for the development of India. The abundance of minerals such as coal, iron ore, copper, mica, bauxite, limestone, and uranium has established Jharkhand as one of the leading mineral-rich states in the country. These natural resources play a crucial role in various industries, making Jharkhand a significant contributor to India's economic growth.The mining sector in Jharkhand has been a key driver of industrialization and infrastructure development in the region and beyond. The state's coal reserves, particularly in areas like Dhanbad and Jharia, have fueled the growth of the thermal power sector, providing energy to power industries and households across the country. Iron ore deposits in places like Singhbhum have been instrumental in supporting the steel industry, a backbone of India's manufacturing sector.The extraction and processing of these minerals have created employment opportunities for thousands of people in Jharkhand, contributing to the state's socio-economic development. However, it is essential to ensure that this wealth is managed sustainably and judiciously to avoid environmental degradation and protect the rights of local communities.Investments in infrastructure, technology, and skill development are crucial to harnessing Jharkhand's mineral wealth effectively. The government and industry stakeholders must work together to ensure that mining activities are conducted responsibly, taking into account environmental conservation and social welfare. Additionally, promoting downstream industries and value addition to raw minerals can further enhance the value derived from these resources.In conclusion, Jharkhand's mineral wealth has the potential to drive the transformation of India into a more developed and prosperous nation. By leveraging these natural resources sustainably and innovatively, Jharkhand can continue to be a catalyst for 'Vikshit Bharat' - a developed India that prioritizes inclusive growth, environmental sustainability, and social progress.